2017
DOI: 10.2337/db16-1587
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cdk5 Promotes β-Cell Differentiation From Ductal Progenitors

Abstract: Inhibition of notch signaling is known to induce differentiation of endocrine cells in zebrafish and mouse. After performing an unbiased in vivo screen of ∼2,200 small molecules in zebrafish, we identified an inhibitor of Cdk5 (roscovitine), which potentiated the formation of β-cells along the intrapancreatic duct during concurrent inhibition of notch signaling. We confirmed and characterized the effect with a more selective Cdk5 inhibitor, (R)-DRF053, which specifically increased the number of duct-derived β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 48 publications
1
38
0
Order By: Relevance
“…CDK5 has been investigated in terminally differentiated cells, such as neurons and neuroendocrine cells (10,11). In synapses, phosphorylation of dynamin 1 by CDK5 is crucial for regulation of endocytosis, and dynamin 1 is phosphorylated at S774 and S778 in rats and sheep (16) as well as T780 in bovine (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDK5 has been investigated in terminally differentiated cells, such as neurons and neuroendocrine cells (10,11). In synapses, phosphorylation of dynamin 1 by CDK5 is crucial for regulation of endocytosis, and dynamin 1 is phosphorylated at S774 and S778 in rats and sheep (16) as well as T780 in bovine (17).…”
Section: Discussionmentioning
confidence: 99%
“…The role of CDK5 has been mostly studied in terminally differentiated cells, including neurons and neuroendocrine cells. CDK5 contributes to neurite outgrowth, neuronal migration, and neuronal and β cell differentiation (10,11). In addition, it has recently been demonstrated that CDK5 is highly expressed in several cancer cell lines and tissues, suggesting this kinase is functionally associated with tumorigenesis and/or malignancy (12).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that growth factors suppress insulin expression by additional mechanisms as well as promoting phosphorylation of Ngn3 protein and thereby restricting its ability to drive the differentiation programme. Thus, the incorporation of phosphomutant Ngn3 and/or cdk inhibitors alongside further manipulation of the growth factor environment could be explored to further increase efficiency of β-cell generation in other in vitro reprogramming protocols 28 , 31 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin-dependent kinase 5 regulatory subunit associated protein 1-like 1 (CDKAL1) gene encodes cyclin-dependent kinase 5 regulatory subunit-associated protein 1 (CDK5RAP1)-like 1,which is homologous to the CDK5RAP1, inhibitor of the CDK5 kinase through the inhibition of the CDK5 activator p35 [5,6]. CDK5 is a serine/threonine protein kinase which is involved in the glucose-dependent regulation of the insulin secretion, therefore, it plays a tolerant role in the pathophysiology of β-cell dysfunction and predisposition to T2DM [7,8].…”
Section: Backgroudmentioning
confidence: 99%